Saberes ancestrales y patrimonio alimentario de la Parroquia Honorato Vásquez, Cantón Cañar. - Avilés Peñafiel, Carolina Elizabeth (2022)
The Honorato Vásquez parish has a great food wealth characterized by agriculture and by the consumption and production of ancestral foods, and that through them the identity of its people is transmitted, however, over the years due to various Factors there has been a process of acculturation in the way of eating and the consumption of traditional and characteristic foods of the parish. With this research, the problems that are related to food heritage can be evidenced and its objective is to determine the relationship that exists with ancestral knowledge. For the development of the research, several tools and instruments were used, the dimensions and indicators were determined based on the elaboration of the problem tree and in turn with the operationalization of each of the variables. Data on both the independent and dependent variables could be obtained through surveys previously validated by experts, which were subsequently processed with the SPSS statistics 22 programs. The reliability of the instruments could be determined through Cronbach's alpha with an excellent degree of reliability. of 0.930 for the independent variable and an Acceptable degree of reliability of 0.711 for the dependent variable and using the Chi-Square method, hypothesis testing was developed, as well as the development of conclusions and recommendations.